PREVALENCE OF DEPRESSION AND ANXIETY AMONG COPD PATIENTS AND ASSOCIATION WITH CAT SCORE - AYUB, S; EJAZ, T; EJAZ, A; KHAN, JA; TAREEN, S (Biological and Clinical Sciences Research Journal, 2024)
Chronic obstructive pulmonary disease (COPD) is a global health problem associated with considerable mortality and morbidity. Objective: This study aimed to determine the prevalence of anxiety and depression among COPD patients living in and to evaluate the associated factors. Furthermore, the utility of the CAT score in predicting depression was also assessed. Methodology: This Prospective observational study was conducted at Aga Khan University Hospital Karachi and Aria Institute of Medical Sciences, Quetta, after approval from the ethical review committee for sample size calculation WHO calculator, based on the prior prevalence of COPD in 10.6% of Pakistani general population. Data were collected from 125 patients through a non-probability consecutive sampling technique. Results: Data were collected from 125 patients according to inclusion and exclusion criteria with a male predominance (96 males, 76.8%) compared to females (29 females, 23.2%). The majority of the participants were ex-smokers (104, 83.2%), followed by those who never smoked (13, 10.4%) and current smokers (8, 6.4%). The mean age of the participants was 64.1 years (±7.01), with an age range from 40 to 95 years. The descriptive statistics for anxiety scores among the 125 COPD patients indicate a mean score of 1.35 with a standard deviation of 0.46. Conclusion: It is concluded that a significant proportion of COPD patients experience high levels of anxiety (70.4%) and depression (67.2%). The chi-square test revealed no significant association between these conditions, indicating they occur independently.